2016
DOI: 10.1111/1440-1681.12633
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of lipid peroxidation and inflammation in short‐term glycerol‐induced acute kidney injury in rats

Abstract: Rhabdomyolysis is characterised by acute kidney injury (AKI) resulting from skeletal muscle injury. Lipid peroxidation-mediated oxidant injury and pro-inflammatory cytokine-mediated inflammatory response play critical roles in the pathogenesis of rhabdomyolysis-induced AKI. The present study aimed to investigate the short-term effects of both lipid peroxidation and inflammatory responses on rhabdomyolysis-induced AKI in a rat model of glycerol-induced rhabdomyolysis. Rhabdomyolysis was induced by the intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The mechanism of rhabdomyolysis‐induced AKI is proposed as follows: the skeletal muscle cell membrane is injured, Mb in skeletal muscle leaks into the blood, Mb accumulates in the kidney cells, and oxidative stress‐induced kidney injury caused via Mb redox cycling generates oxidized lipids. These oxidized lipids propagate renal tissue injury (Boutaud & Roberts, ; Nara et al, ). Thus, Mb leaked from skeletal muscle is known to be a key mediator for AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of rhabdomyolysis‐induced AKI is proposed as follows: the skeletal muscle cell membrane is injured, Mb in skeletal muscle leaks into the blood, Mb accumulates in the kidney cells, and oxidative stress‐induced kidney injury caused via Mb redox cycling generates oxidized lipids. These oxidized lipids propagate renal tissue injury (Boutaud & Roberts, ; Nara et al, ). Thus, Mb leaked from skeletal muscle is known to be a key mediator for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…BSO, Lbuthionine-(S,R)-sulfoximine; GSH, glutathione; GSSG, glutathione disulfide generates oxidized lipids. These oxidized lipids propagate renal tissue injury (Boutaud & Roberts, 2011;Nara et al, 2016). Thus, Mb leaked from skeletal muscle is known to be a key mediator for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative injury mediated by lipid peroxidation is an unfavorable factor for AKI [ 85 ], while lipid peroxidation inhibition can alleviate kidney injury [ 86 ]. One month before Dixon proposed ferroptosis, some researchers found that deferoxamine (DFO), which was not listed as a ferroptosis inhibitor then, could inhibit lipid peroxidation and renal tubular epithelial cell necrosis to prevent renal failure [ 87 ].…”
Section: Ferroptosis and Akimentioning
confidence: 99%
“…However, that adaptation resulted in some technical variations, both in the storage media used (10% or 15% glycerol, or D5W alone) and in the strategy of filtration to remove particulate (multistage filtration through a 860 µm and, then, a 190 µm filter, or individual filtrations through 100 µm or 70 µm filters) 13,14,15 . The injection of glycerol alone could potentially cause harm, given that 25%-50% glycerol injections have been used as a rodent model of renal injury 16,17,18,19,20 . To avoid unintended side effects of glycerol, the cecal slurry stock preparation for mice in this study is frozen in D5W without glycerol, and tests of bacterial viability from storage at -80 °C are performed.…”
Section: Introductionmentioning
confidence: 99%